Digital Diplomacy and its Prospect for Nepal - Shrestha, Madhavji (Journal of Foreign Affairs, 2022)
Change in any dimension ushers in new dawn. The fast-paced advancement of the information, communication, and technological sectors has affected several traditional areas. One area that has been highly impacted is the domain of diplomacy. The digital imprints in diplomacy have shifted the diplomatic activities to a virtual platform. However, there have been difficulties in defining the idea of “digital diplomacy”. This study points out the efforts of the scholars and researchers towards defining the domain of digital diplomacy. Therefore, the primary aim of the article is to explore different facets of digital diplomacy. It explains how the digitization process began in diplomacy and whether digitization has displaced or complemented the traditional forms of diplomacy. The study has highlighted the supremacy of human beings over the new technologies in diplomacy. It deals with the policy goals of digital diplomacy and emphasizes the United Nations’ attempt to enhance the same. Finally, the study has explored digital diplomacy of Nepal and makes policy recommendations for enhancing digital diplomacy in Nepal. The study has used secondary resources, including books, journals, and online media platforms. The information and ideas are put in array for the coherent presentation of the study with the adoption of analytical process.